Evaluation of a 7-year schoolbased community dental hygiene programme in Portugal by high school teachers - VA Assunc¸a˜o (Journal compilation 2008 Blackwell Munksgaard, 2008)
To obtain high school teachers evaluation of a Community Dental Hygiene programme, developed as part of a clinical trial designed to assess the safety of low-level mercury exposure from amalgam restorations.